Hubungan Tingkat Stres dengan Terjadinya Gastritis pada Mahasiswa Semester III Keperawatan UMS Menjelang Ujian Objective Structur Clinical Examination (OSCE) - Dewi Vinata; Okti Sri Purwanti (Universitas Malahayati Lampung, 2025)
ABSTRACT Approaching the implementation of OSCE at the Faculty of Health Sciences, Muhammadiyah University of Surakarta, many students face significant stress problems. The pressure to prepare for this practical exam often causes excessive anxiety, which can have an impact on physical and mental health. Type of quantitative research. This study is an analytical observational study, a cross-sectional approach to the population of 168 students of Nursing Science Bachelor's degree students in Semester 3 who will take the OSCE exam. The number of samples in this study was 130 respondents, the sampling technique used was the Simple random sampling technique. This study was conducted in December 2024 - January 2025 in front of the courtyard of the Faculty of Health Sciences, 1st Floor, Muhammadiyah University of Surakarta. The measuring instrument/instrument was a questionnaire (closed questionnaire). Data analysis was univariate (frequency distribution) and bivariate (chi square). The majority of students experience stress Normal level 6 (4.6%) students, mild stress level 6 (4.6%) students, moderate stress level 30 (23.1%), severe stress level 42 (32.3%) and very severe stress level 46 (35.4%). Students who have high gastritis are 15 (11.5%) students, moderate gastritis 86 (66.2%) and low gastritis 29 (22.3%) students. The results of the Spearman test showed a significance value of 0.001 which indicates a relationship between stress and the occurrence of gastritis in students. Keywords: Gastritis, Osce, Stress ABSTRAK Menjelang pelaksanaan OSCE di Fakultas Ilmu Kesehatan Universitas Muhammadiyah Surakarta, banyak mahasiswa menghadapi masalah stres yang signifikan. Tekanan untuk mempersiapkan ujian praktik ini seringkali menyebabkan kecemasan yang berlebihan, yang dapat berdampak pada kesehatan fisik dan mental. Jenis penelitian kuantitatif. Penelitian ini bersifat observasional analitik, pendekatan cross sectional populasi mahasiswa S1 Ilmu Keperawatan Semester 3 yang berjumlah 168 Mahasiswa yang akan mengikuti ujian OSCE. Jumlah sampel dalam penelitian ini sebanyak 130 responden, teknik sampling yang digunakan adalah dengan cara teknik Simple random sampling. Penelitian ini telah dilakukan pada Desember 2024 - Januari 2025 di depan halaman Fakultas Ilmu Kesehatan Lantai 1 Universitas Muhamamadiyah Surakarta. Alat ukur/Instrumen berupa kuesioner (angket tertutup). Analisis data secara univariat (distribusi frekuensi) dan bivariat (chi square). Mayoritas Mahasiswa mengalami stres Tingkat normal 6 (4.6%) mahasiswa, Tingkat stress ringan 6 (4.6%) mahasiswa, tingkat stress sedang 30 (23.1%), Tingkat stress berat 42 (32.3%) dan stress Tingkat sangat berat 46 (35.4%). Mahasiswa yang memiliki gastritis tinggi sebanyak 15 (11.5%) mahasiswa, gastritis sedang 86 (66.2%) dan gastritis rendah 29 (22.3%) mahasiswa. Hasil Uji spearman menunjukan nilai signifikasi sebesar 0.001 yang menunjukan adanya hubungan antara stres dengan terjadinya gastritis pada mahasiswa. Kata Kunci: Gastritis, Osce, Stress